Answer:
1 time
Step-by-step explanation:
Given numbers are 54 and 36.
The greatest common divisor of 54 and 36 = 18
So, [tex]a_1 = 18[/tex].
The least common multiple of 54 and 36 = 108
So, [tex]b_1 = 108[/tex].
As 54 is replaced by [tex]a_1[/tex] and 36 is replaced by [tex]b_1[/tex], so after applying the given procedure, the new number is
[tex](a_1, b_1)=(18, 108)\cdots(i)[/tex]
Now, apply the same procedure, to get [tex]a_2[/tex] and [tex]b_2[/tex].
The greatest common divisor of 18 and 108 = 18
So, [tex]a_2 = 18[/tex].
The least common multiple of 18 and 108 = 108
So, [tex]b_2 = 108[/tex].
As [tex]a_1[/tex] is replaced by [tex]a_2[/tex] and [tex]b_1[/tex] is replaced by [tex]b_2[/tex], so after applying the given procedure, the new number is
[tex](a_2, b_2)=(18, 108)[/tex] which is the same as in equation (i)
Hence, after applying the procedure 1 time after [tex](a_1, b_1)[/tex], the obtained number [tex](a_2, b_2)[/tex] is the same as [tex](a_1,b_1)[/tex].